2013
DOI: 10.1002/jgrd.50226
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Whole Atmosphere Community Climate Model simulations of ozone during Arctic winter 2004–2005

Abstract: [1] The work presented here evaluates polar stratospheric ozone simulations from the Whole Atmosphere Community Climate Model (WACCM) for the Arctic winter of [2004][2005]. We use the Specified Dynamics version of WACCM (SD-WACCM), in which temperatures and winds are nudged to meteorological assimilation analysis results. Model simulations of ozone and related constituents generally compare well to observations from the Earth Observing System Microwave Limb Sounder (MLS). At most times, modeled ozone agrees wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
103
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 66 publications
(109 citation statements)
references
References 76 publications
6
103
0
Order By: Relevance
“…Chemical ozone loss commenced around 12 January (Fig. 3d), consistent with findings from previous studies (e.g., Manney et al, 2006;Brakebusch et al, 2013), and hourly loss rates peaked around 30 January at 500 K (∼ 20 km) and 20 February at 450 K (∼ 18 km). When scaled by the hours of sunlight available, the 450 K losses in late February are more significant than those at 500 K in the late January period (Fig.…”
Section: Estimating Integrated Ozone Losses For Each Winter/springsupporting
confidence: 79%
See 1 more Smart Citation
“…Chemical ozone loss commenced around 12 January (Fig. 3d), consistent with findings from previous studies (e.g., Manney et al, 2006;Brakebusch et al, 2013), and hourly loss rates peaked around 30 January at 500 K (∼ 20 km) and 20 February at 450 K (∼ 18 km). When scaled by the hours of sunlight available, the 450 K losses in late February are more significant than those at 500 K in the late January period (Fig.…”
Section: Estimating Integrated Ozone Losses For Each Winter/springsupporting
confidence: 79%
“…This method was first developed by Manney et al (1995b, a) to quantify ozone loss during the 1992/93 Arctic winter, using a trajectory-based passive ozone estimate, and has been subsequently applied in similar form to other seasons (e.g., Manney et al, 1996aManney et al, , b, 1997Manney et al, , 2003Schoeberl et al, 2002). Where a full chemistry transport model is employed (e.g., Deniel et al, 1998;Goutail et al, 1999;Singleton et al, , 2007; L. Grooß and Müller, 2007;Rösevall et al, 2008;Jackson and Orsolini, 2008;Kuttippurath et al, , 2012Feng et al, 2011;Brakebusch et al, 2013), ozone loss can be estimated by comparing the modeled passive ozone to both the ozone simulated by the same model and to observed ozone, with comparisons between the latter two fields typically used to quantify the overall accuracy of the model calculations (both from the dynamical and chemical perspective). The passive subtraction approach can be taken a stage further by considering a "pseudo passive" ozone tracer , subject to both dynamical and gas-phase chemistry influences, but not the losses due to chlorine activated through heterogeneous processes.…”
Section: Introductionmentioning
confidence: 99%
“…Sensitivity simulations or adjustments based on observations concerning, for instance, the partitioning between STS and NAT and/or the limit for the NAT number density as done by Brakebusch et al (2013) and Wegner et al (2013) would help to find the best model set-up for simulating Arctic PSCs. Further, the results derived here and upcoming sensitivity simulations will serve as a benchmark for the development of the PSC parameterization in other atmospheric models, such as ICON-ART (ICOsahedral Nonhydrostatic Model -Aerosols and Reactive Trace gases), and will help to improve the performance of EMAC in future model intercomparison studies.…”
Section: Discussionmentioning
confidence: 99%
“…The lower stratospheric processes that lead to chemical ozone destruction include the development of polar stratospheric clouds (PSCs), denitrification via sedimentation of PSCs, and conversion of inert chlorine reservoirs to ozone-destroying forms by reactions on the surfaces of PSCs (e.g., Solomon, 1999). Because these phenomena depend critically on temperatures and winds throughout the lower stratosphere (e.g., WMO, 2011WMO, , 2015Brakebusch et al, 2013;Manney et al, 2011;Sinnhuber et al, 2011;and references therein), diagnostics related to ozone loss require fields (e.g., winds) and data coverage (e.g., vertically resolved, hemispheric, multiannual) that cannot be obtained from individual measurement systems such as satellites and radiosonde networks. As a result, the global analyses of meteorological fields provided by data assimilation systems (DAS) that combine many of these measurements are invaluable for polar processing and ozone loss studies.…”
Section: Introductionmentioning
confidence: 99%
“…Sinnhuber et al (2011) found that reducing the temperatures from the ECMWF operational analyses by 1 K in CTM runs for the 2010/2011 Arctic winter resulted in a substantial increase in ozone loss. Brakebusch et al (2013) reduced GEOS-5 (Goddard Earth Observing System model, version 5) temperatures by 1.5 K in a Whole Atmosphere Community Climate Model simulation of ozone for the 2004/2005 Arctic winter; applying this temperature bias improved the agreement of simulated ozone with measurements from the Aura Microwave Limb Sounder satellite instrument. In other cases, some DAS analyses have been shown to have significant shortcomings for use in polar processing and ozone loss research.…”
Section: Introductionmentioning
confidence: 99%